Religious and Moral Educational Values in The Novel Ta'aruf Dalam Sunyi By Diana Fitria Irma Martina - Martina, Irma; Wardiah, Dessy; Rukiyah, Siti (Program Studi Pendidikan Bahasa Inggris, Universitas Pendidikan Muhammadiyah Sorong, 2023)
The purpose of this research is to describe the religious and moral educational values in the novel Ta'aruf Dalam Sunyi (A Sociological Review of Literature). This is qualitative research with a descriptive method. The data analysis technique uses content analysis with the research object of the novel Ta'aruf Dalam Sunyi by Diana Fitria. Data collection techniques using library research. The data validation technique uses technical triangulation. The results of the study show that the total religious educational values and moral educational values in the novel with the total 41. In the form of religious educational values totalling 19 data points consisting of the value of human relations with God and human relations with other human beings. The moral educational values total 22 data points, consisting of honest values, the values of determination and commitment, the values of cooperation, and the values of responsibility.